Impact of Labour Productivity Differences on Urban-Rural Integration Development and Its Spatial Effect: Evidence from a Spatial Durbin Model - Wei Wang; Yulin Zhu (Complexity)
Lewis’ dual economic structure theory holds that differences in labour productivity affect urban-rural integration development. Based on this theory, this paper analyses the spatial mechanism of labour productivity affecting the development of urban-rural integration. A multidimensional index system is constructed to estimate the degree of urban-rural integration development, and a spatial Durbin model is used to quantitatively analyse the spatial effect between the difference in labour productivity and the development of urban-rural integration. The results show that there is a significant positive spatial agglomeration phenomenon in urban-rural integration in the Yangtze River Economic Belt. The convergence of labour productivity will not only promote local urban-rural integration but also inhibit the urban-rural integration development of other administrative divisions, but it can still play a positive role in promoting the urban–rural integration development of the whole region. Finally, based on the above research conclusions, this paper puts forward three policy suggestions: optimizing the human capital structure, promoting rural industrial integration, and exploring the land reform system.